BRASH syndrome: а clinical case - D. D. Shalaeva; K. G. Pereverzeva; O. A. Fomina; S. S. Yakushin (Рациональная фармакотерапия в кардиологии)
The article describes a clinical case of BRASH syndrome in patient M., born in 1938, suffering from hypertension and diabetes mellitus. The patient took bisoprolol, eplerenone, azilsartan medoxomil, lercanidipine hydrochloride daily. She was admitted to the hospital complaining of weakness, eyes darkening, nausea, short-term loss of consciousness, rare pulse, diarrhea the day before. During the examination, she was diagnosed with severe sinus bradycardia (38 beats/min) and transient first-degree atrioventricular (AV) block, stage 4 chronic kidney disease of with hyperkalemia (potassium 5.53-6.12 mmol/l). Pulse-reducing drugs, blockers of the renin-angiotensin-aldosterone system were canceled for the patient, 0.9% sodium chloride solution and furosemide were prescribed. The patient was discharged in a satisfactory condition. This clinical example meets the criteria of BRASH syndrome, since against the background of taking an AV node blocker in a small dose, a patient with chronic kidney disease with mild to moderate hyperkalemia developed severe sinus bradycardia and transient grade 1 AV block. The trigger factors for BRASH syndrome development of were azilsartan medoxomil and eplerenone intake, as well as hypovolemia due to diarrhea.